Adsorption of Cadmium(II) Ions from Aqueous Solutions Using Calcium Molybdate - De Cássia Pereira, Sandra; Das Graças Barbosa, Amanda; De Figueiredo, Alberthmeiry Teixeira; Morita Barrado, Cristiano; Nunes Alves, Vanessa; Longo, Elson [UNESP] (Trans Tech Publications, 2022)
The presence of toxic metals in aquatic environments poses serious problems for ecosystems and especially for human health. Numerous types of metal oxides have been used to remove these metals and other toxic organic compounds, using adsorption systems. In this work, CaMoO4 was synthesized via coprecipitation and processed for different periods of time using a microwave-assisted hydrothermal system. It was possible to synthesize CaMoO4 at room temperature without any heat treatment. In addition, small processing times in HTMW were able to produce CM with different morphologies. The effect of the reaction time on the morphology of the product and particle size was examined in SEM images. A plausible CaMO4 formation mechanism was proposed based on time and temperature parameters. The potential application of CaMO4 as an adsorbent in water treatment was also investigated and this material exhibited a favorable adsorption performance in the fast removal of cadmium(ii) ions from aqueous solution of 1 mg L-1 concentration. So, CM showed a promising potential for use in environmental remediation.
Keywords: Adsorption; Calcium molybdate; Hydrothermal-microwave; Scheelite